POLITIK UANG DAN RISIKO KORUPSI YANG MENGANCAM PERTAHANAN NIRMILITER - A. Muh Alif Ranggong; Zainal Abidin; Arifuddin Uksan (Jurnal Education and Development, 2023)
However, the change to a democratic political system in Indonesia that previously adhered to an authoritarian system does not mean that the former authoritarian system was previously lost easily and quickly. would-be leaders who legalized all means to make their way up the palace seat. One of them is to use the practice of money politics. Money politics or also known as money politics, as the name suggests, is a political practice that uses encouragement and injection of funds to carry out its political agenda to run smoothly. Money politics comes in many forms, such as vote buying, vote brokers, and political corruption. Corruption entrenched in the government will cause systematic losses that will end up inflicting huge losses on the people especially the lower middle class Of the economy With so many cases of corruption continuing to develop, this will threaten the resilience of our country. The political dowry of money can be in the form of basic food assistance, infrastructure repairs to "dawn attacks" that give money directly to the people. With the level of corruption in this country, corruption is one of Indonesia's defense weaknesses.